A portable source-informed machine learning framework for predicting heavy metals in legacy smelting sites with strong spatial heterogeneity - Xu Cao; Yan Liang; Yawei Zhao; Tianhuan Chen; He Huang; Tian Xie (Journal of Hazardous Materials, 2026)

A proton-relay strategy with K-modulated N/P proton pairs over Ru-based catalysts for efficient ammonia decomposition - Shuyu Chen; Rui Chen; Liang Wang; Haibo Tang; Rui Wang; Tian Tian; Yawei Zhou; Zihan Meng; Haolin Tang (Chemical Engineering Journal, 2026)

Microdroplet induced catalyst surface fields boost hydroxyl radical generation and its application - Ange Zhu; Jingkang Gao; Yunjun Mei; Mengxi Cao; Fengjie Chen; Bolei Chen; Yong Liang; Yawei Wang (Journal of Hazardous Materials, 2026)

Excellent infrared radiation performance and significant energy-saving efficiency of LaAlO3 ceramics via Ca2+/Co2+ co-doping - Qinghu Wang; Yangxi Liu; Guoping Wei; Liang Huang; Xueqing Wang; Shaobai Sang; Yibiao Xu; Xiong Liang; Yawei Li; Jiangtao Li; Olena Volkova; Emad M.M. Ewais; et al. (Chemical Engineering Journal, 2026)

Investigation on the effect of nanocellulose-enhanced short-chain fluorocarbon foam parameters on gasoline pool fire extinguishing performance - Yawei Lu; Jiahao Lai; Shaolin Liang; Xingyan Cao; Zhirong Wang; Yangqing Zhou (Process Safety and Environmental Protection, 2025)

Removal of insoluble barium scales from reverse osmosis membranes by grafting molecular springs - Xin Wen; Yuyan Hai; Rui Ma; Xu Liang; Yawei Duan; Jingyun Chen; Hui Wei; Rihua Xiong (Desalination, 2025)

Improved degradable, mechanical, and osteoimmunity-regulating performances of additively manufactured Zn-Mg alloy with heterogeneous microstructure for augmented bone regeneration - Zhengjun Lin; Luxin Liang; Yawei Li; Yanlin Wu; Jing Li; Bing Wang; Chao Chen; Tang Liu (Chemical Engineering Journal, 2025)

Sustainable Ca(OH)2 deacidifiers derived from waste eggshells for free fatty acids removal: characterization, performance and thermodynamics - Yawei Wang; Chao He; Gang Li; Xinxin Liu; Liang Liu; Youzhou Jiao (Environment, Development and Sustainability, 2025)

Mechanisms of antifungal activity of ehimensin F6 produced by Paenibacillus ehimensis HD against Penicillium expansum - Yuqing Huang; Dandan Liu; Yahui Liu; Ziwei Jia; Tengteng Zhao; Zhen Zhao; Yawei Ning; Xiaohui Liang; Zhixin Wang (International Journal of Food Microbiology, 2025)

Stability analysis of karst anti dip rock slope induced by underground coal mining - A case study of Jiguanling landslide, China - Zuliang Zhong; Erwei Liang; Nanyun Wang; Yawei Xu (Journal of Mountain Science, 2025)

Advances in regional-scale crop growth and associated process modeling - Wenfeng Liu; Yawei Bai; Taisheng Du; Mengxue Li; Hong Yang; Shichao Chen; Chuanbin Liang; Shaozhong Kang (Science China Earth Sciences, 2025)

Recent advances in groundwater pollution research using machine learning from 2000 to 2023: A bibliometric analysis - Xuan Li; Guohua Liang; Bin He; Yawei Ning; Yuesuo Yang; Lei Wang; Guoli Wang (Environmental Research, 2025)

A hybrid TCN-BiLSTM short-term load forecasting model for ship electric propulsion systems combined with multi-step feature processing - Shuo Pang; Liang Zou; Li Zhang; Hui Wang; Yawei Wang; Xingdou Liu; Jundao Jiang (Ocean Engineering, 2025)

Molecular designing of potential environmentally friendly PFAS based on deep learning and generative models - Ying Yang; Zeguo Yang; Xudi Pang; Huiming Cao; Yuzhen Sun; Ling Wang; Zhen Zhou; Pu Wang; Yong Liang; Yawei Wang (Science of The Total Environment, 2024)

Low-permittivity BaCuSi4O10-based dielectric Ceramics: An available solution to connect low temperature cofired ceramic technology and millimeter-wave communications - Wei Wang; Xin Wang; Jian Bao; Jiapei Jiang; Zhen Fang; Biaobing Jin; Zhongqi Shi; Moustafa Adel Darwish; Yawei Chen; Qixin Liang; Meirong Zhang; Diming Xu; et al. (Chemical Engineering Journal, 2024)

Alternating wet and dry irrigation cycles enhance the nitrogen “cache” function of duckweed in a rice-duckweed system - Weixuan Liu; Junzeng Xu; Yawei Li; Xiaoyin Liu; Ning Gao; Zeeshan Ahmed; Yihao Peng; Hao Liang; Qianjing Jiang; Yong He (Agriculture, Ecosystems & Environment, 2024)

Macaque Brainnetome Atlas: A multifaceted brain map with parcellation, connection, and histology - Yuheng Lu; Yue Cui; Long Cao; Zhenwei Dong; Luqi Cheng; Wen Wu; Changshuo Wang; Xinyi Liu; Youtong Liu; Baogui Zhang; Deying Li; Bokai Zhao; et al. (Science Bulletin, 2024)

Hydrothermal liquefaction of pig carcasses to biofuel: A techno-economic analysis - Youzhou Jiao; Chao Chang; Gaojie Xu; Chao He; Xinxin Liu; Gang Li; Yawei Wang; Xiaohui Pan; Guizhuan Xu; Qibin Li; Liang Liu (Process Safety and Environmental Protection, 2024)

TREM2 Deficiency Aggravates NLRP3 Inflammasome Activation and Pyroptosis in MPTP-Induced Parkinson’s Disease Mice and LPS-Induced BV2 Cells - Peiting Huang; Zhanyu Zhang; Piao Zhang; Jiezhu Feng; Jianwei Xie; Yinjuan Zheng; Xiaomei Liang; Baoyu Zhu; Zhenzhen Chen; Shujun Feng; Lijuan Wang; Jiahong Lu; et al. (Molecular Neurobiology, 2024)
Microglia-mediated neuroinflammation plays a crucial role in the pathogenesis of Parkinson’s disease (PD). Triggering receptor expressed on myeloid cells 2 (TREM2) confers strong neuroprotective effects in PD by regulating the phenotype of microglia. Recent studies suggest that TREM2 regulates high glucose-induced microglial inflammation through the NLRP3 signaling pathway. This study aimed to investigate the effect of TREM2 on NLRP3 inflammasome activation and neuroinflammation in PD. Mice were injected with AAV-TREM2-shRNA into both sides of the substantia nigra using a stereotactic injection method, followed by intraperitoneal injection of MPTP to establish chronic PD mouse model. Behavioral assessments including the pole test and rotarod test were conducted to evaluate the effects of TREM2 deficiency on MPTP-induced motor dysfunction. Immunohistochemistry of TREM2 and tyrosine hydroxylase (TH), immunohistochemistry and immunofluorescence Iba1, Western blot of NLRP3 inflammasome and its downstream inflammatory factors IL-1β and IL-18, and the key pyroptosis factors GSDMD and GSDMD-N were performed to explore the effect of TREM2 on NLRP3 inflammasome and neuroinflammation. In an in vitro experiment, lentivirus was used to interfere with the expression of TREM2 in BV2 microglia, and then lipopolysaccharide (LPS) and adenopterin nucleoside triphosphate (ATP) were used to stimulate inflammation to construct a cellular inflammation model. The expression differences of NLRP3 inflammasome and its components were detected by qPCR and Western blot. In vivo, TREM2 knockdown aggravated the loss of dopaminergic neuron and the decline of motor function. After TREM2 knockdown, the number of activated microglia was significantly increased, and the expression of cleaved caspase-1, NLRP3 inflammasome, IL-1β, GSDMD, and GSDMD-N was increased. In vitro, TREM2 knockdown aggravated the inflammatory response of BV2 cells stimulated by LPS and promoted the activation of NLRP3 inflammasome through the NF-κB pathway. In addition, TREM2 knockdown also promoted the expression of TLR4/MyD88, an upstream factor of the NF-κB pathway. Our vivo and vitro data showed that TREM2 knockdown promoted NLRP3 inflammasome activation and downstream inflammatory response, promoted pyroptosis, and aggravated dopaminergic neuron loss. TREM2 acts as an anti-inflammatory in PD through the TLR4/MyD88/NF-κB pathway, which extends previous findings and supports the notion that TREM2 ameliorates neuroinflammation in PD.

Nanocatalyst-triggered cascade immunoassay: Multi-model immunochromatography assay for sensitive detection of Salmonella typhimurium - Xuechi Yin; Jingxin Hou; Jing Guo; Jiawei Li; Di Yang; Linpin Luo; Leina Dou; Yawei Liang; Yanru Wang; Jianlong Wang; Daohong Zhang (Chemical Engineering Journal, 2023)

Distribution characteristics of photoinitiators and their flux estimation from the Pearl River Delta to the coastal waters of the South China Sea - Yuqing He; Zibin Pan; Xinxin Liang; Ruiman Xie; Yuying Sun; Juan Li; Yawei Wang; Lixi Zeng (Journal of Environmental Sciences, 2023)

Isomer-specific perfluoroalkyl acids accumulation, excretion and maternal transfer to eggs in chickens around a fluorochemical manufactory in China - Yan Gao; Boyu Song; Anen He; Chao Liu; Yao Lu; Juan Li; Jianjie Fu; Yong Liang; Yawei Wang (Science of The Total Environment, 2023)

Innovative calcium-doped layered yttrium hydroxides for rapid and efficient removal of fluoride from aqueous solutions: Insight into adsorption mechanism - Ying Liang; Fengjie Chen; Meng Zhang; Lufeng Chen; Yu Xia; Zhen Zhou; Bolei Chen; Lixia Zhao; Yong Liang; Yawei Wang (Journal of Environmental Chemical Engineering, 2023)

Novel strategies and approaches toward toxicity assessment: a key factor for safety assessment and management of per- and polyfluoroalkyl substances - Yao Lu; Chunyan Zhao; Hanyong Peng; Jinghua Hao; Chunyang Liao; Yong Liang; Yawei Wang; Guibin Jiang (Science Bulletin, 2023)

DLGAP1-AS2 promotes estrogen receptor signalling and confers tamoxifen resistance in breast cancer - Xiaoli Liang; Yang Zhao; Zeng Fang; Nan Shao; Duanyang Zhai; Mengmeng Zhang; Liang Yu; Yawei Shi (Molecular Biology Reports, 2022)

Design and evaluation of chitosan-amino acid thermosensitive hydrogel - Jianan Tong; Huiyun Zhou; Jingjing Zhou; Yawei Chen; Jing Shi; Jieke Zhang; Xinyu Liang; Tianyuan Du (Marine Life Science & Technology, 2022)

Identification of HvLRX, a new dehydration and light responsive gene in Tibetan hulless barley (Hordeum vulgare var. nudum) - Junjun Liang; Haili Zhang; Ling Yi; Yawei Tang; Hai Long; Maoqun Yu; Guangbing Deng (Genes & Genomics, 2021)

Identification and candidate gene mining of HvSS1, a novel qualitative locus on chromosome 6H, regulating the uppermost internode elongation in barley (Hordeum vulgare L.) - Xi Pu; Yanyan Tang; Meihao Zhang; Tao Li; Xvebing Qiu; Juanyu Zhang; Jinhui Wang; Lilan Li; Zhao Yang; Yan Su; Haili Zhang; Junjun Liang; et al. (Theoretical and Applied Genetics, 2021)

An Analytical Risk Analysis Method for Reservoir Flood Control Operation Considering Forecast Information - Yawei Ning; Wei Ding; Guohua Liang; Bin He; Huicheng Zhou (Water Resources Management, 2021)

Bioaugmentation-assisted phytoremediation of manganese and cadmium co-contaminated soil by Polygonaceae plants (Polygonum hydropiper L. and Polygonum lapathifolium L.) and Enterobacter sp. FM-1 - Yi Li; Jiamin Lin; Yuanyuan Huang; Yawei Yao; Xueru Wang; Chengzhao Liu; Ying Liang; Kehui Liu; Fangming Yu (Plant and Soil, 2020)

Carbon pools and fluxes in the China Seas and adjacent oceans - Nianzhi Jiao; Yantao Liang; Yongyu Zhang; Jihua Liu; Yao Zhang; Rui Zhang; Meixun Zhao; Minhan Dai; Weidong Zhai; Kunshan Gao; Jinming Song; Dongliang Yuan; et al. (Science China Earth Sciences, 2018)

A parameter-free progressive TIN densification filtering algorithm for lidar point clouds - Xiaotian Shi; Hongchao Ma; Yawei Chen; Liang Zhang; Weiwei Zhou (International Journal of Remote Sensing, 2018)

Knockout of CTNNB1 by CRISPR-Cas9 technology inhibits cell proliferation through the Wnt/β-catenin signaling pathway - Lihong Guan; Shaoyi Zhu; Yawei Han; Ciqing Yang; Yanli Liu; Liang Qiao; Xiaoying Li; Han Li; Juntang Lin (Biotechnology Letters, 2018)

A Single Nucleotide Polymorphism of Nud Converts the Caryopsis Type of Barley (Hordeum Vulgare L.) - Shuiyang Yu; Hai Long; Guangbing Deng; Zhifen Pan; Junjun Liang; Xingquan Zeng; Yawei Tang; Nyima Tashi; Maoqun Yu (Plant Molecular Biology Reporter, 2016)

Dynamical analysis of periodic bursting in piece-wise linear planar neuron model - Ying Ji; Xiaofang Zhang; Minjie Liang; Tingting Hua; Yawei Wang (Cognitive Neurodynamics, 2015)

Effects of vegetation and soil texture on surface soil moisture retrieval using multi-temporal optical and thermal infrared observations - Pei Leng; Xiaoning Song; Zhao-Liang Li; Yawei Wang; Di Wang (International Journal of Remote Sensing, 2015)

Uncertainty analysis of SPI calculation and drought assessment based on the application of Bootstrap - Yi‐Ming Hu; Zhong‐Min Liang; Yong‐Wei Liu; Jun Wang; Lei Yao; Yawei Ning (International Journal of Climatology, 2015)
The Standardized Precipitation Index ( SPI ) has been widely used to monitor the drought status. In the estimation of SPI , an appropriate probability distribution function ( APDF ) is required to fit precipitation series with different timescales, such as 3‐month, 9‐month and so on. Then the standard normal distribution function is used to transform the cumulative probability derived from APDF to calculate the SPI value. Obviously, the estimation accuracy of SPI particularly depends on the sample that influences the selection of PDF and parameter estimation. However, the size of the observed sample is usually small, and it cannot perfectly present the statistical property of the population, which usually causes the uncertainty on calculation of SPI and in turn results in the uncertainty of drought assessment. Due to the existence of gap between the estimated SPI and the true SPI , when one obtains the estimation of SPI , it is necessary to know the reliability or uncertainty of the estimated SPI . In this article, a new method based on the Bootstrap method was put forward to analyse the impact of sampling uncertainty on the estimation of SPI and drought assessment. Through repeating samples from the original sample, a large number of Bootstrap samples are constructed, and based on each Bootstrap sample, the corresponding estimation of SPI for the given event can be obtained. Therefore, the sampling distribution of SPI for the given event can also be derived, on which both the point estimation and interval estimation of SPI for the given precipitation event can be provided, and the overall assessment of a drought event could be achieved. The case study shows that, compared with the original SPI calculation method, the proposed method not only provides equivalent assessment results, but also has the capability to assess the impact of sampling uncertainty on the uncertainty of SPI calculation and drought assessment.

Multilayer Pressure Containment Model and its Application in Deep Well Fractured Formation - Pei Yang; Mian Chen; Yan Jin; Bing Hou; Yunhu Lu; Chuan Liang; Qianqian Zhu; Yawei Li (Rock Mechanics and Rock Engineering, 2013)

Proteomic survey towards the tissue-specific proteins of mouse mitochondria - Yuan Wang; HaiDan Sun; YaWei Ru; SongYue Yin; Liang Yin; SiQi Liu (Science China Life Sciences, 2011)

Calcineurin Plays an Important Role in the Shell Formation of Pearl Oyster (Pinctada fucata) - Changzhong Li; Yilin Hu; Jian Liang; Yawei Kong; Jing Huang; Qiaoli Feng; Shuo Li; Guiyou Zhang; Liping Xie; Rongqing Zhang (Marine Biotechnology, 2010)